Forms of Activities with a Dog as Modern Types of Physical Recreation - Monika Niewiadomska (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2018)
The rapid civilisational development that took place in the second half of the 20th century, and the resulting changes in the conditions and ways of people's lives brought forth a number of social phenomena, both positive and negative. Physical activities, i.e. any forms of physical effort undertaken voluntarily in leisure time for entertainment and health purposes, contribute greatly to overcoming the dangers of modern civilization. Among these, activities with the participation of a dog are becoming increasingly popular. These activities are exercised by people of all ages in the form of dog sports, as well as for recreational and therapeutic purposes. The aim of the paper is to present various forms of activities with a dog as modern types of physical recreation exercised by people of all ages. Regular exercise with a dog greatly improves the well-being and provides a feeling of harmony and inner peace. It is becoming yet another modern form of activity.